Response to displaced neighbours in a territorial songbird with a large repertoire - Briefer, Elodie; Aubin, Thierry; Rybak, Fanny (Naturwissenschaften, 2009)
International audience Neighbour recognition allows territory owners to modulate their territorial response according to the threat posed by each neighbour and thus to reduce the costs associated with territorial defence. Individual acoustic recognition of neighbours has been shown in numerous bird species, but few of them had a large repertoire. Here, we tested individual vocal recognition in a songbird with a large repertoire, the skylark Alauda arvensis. We first examined the physical basis for recognition in the song, and we then experimentally tested recognition by playing back songs of adjacent neighbours and strangers. Males showed a lower territorial response to adjacent neighbours than to strangers when we broadcast songs from the shared boundary. However, when we broadcast songs from the opposite boundary, males showed a similar response to neighbours and strangers, indicating a spatial categorisation of adjacent neighbours’ songs. Acoustic analyses revealed that males could potentially use the syntactical arrangement of syllables in sequences to identify the songs of their neighbours. Neighbour interactions in skylarks are thus subtle relationships that can be modulated according to the spatial position of each neighbour.